Isothermal and thermomechanical fatigue crack propagation in both virgin and thermally aged Haynes 230. (March 2019) - Ewest, D.; Almroth, P.; Sjödin, B.; Leidermark, D.; Simonsson, K.
Highlights: Thermomechanical fatigue crack propagation tests in addition to isothermal. Thermally aged material tested in additional virgin material. Notched specimens with constant amplitude loading for crack initiation and growth. Tests are numerical simulated to calculate the effective crack driving force, ΔJeff . Good correlations between the numerical and test results. Abstract: Fatigue crack propagation tests under both isothermal and non-isothermal thermomechanical fatigue conditions have been performed on wrought Haynes 230, a ductile combustor material. A number of specimens were thermally aged by pre-straining and subsequent furnace exposure for 3000 h at 600 °C. The tests were performed both under load and strain control, between room temperature and 600 °C. The thermally aged notched specimens show a decrease in the crack initiation life, similar to results previously reported for smooth test specimens at room temperature. For the crack growth rates, the effects of thermal ageing were less pronounced than for crack initiation. Further, the tests have been simulated using the finite element method to calculate the crack driving force, where the plasticity induced crack closure is handled with a full history description. A temperature dependent linear kinematic hardening plasticity law has been adopted for describing the material behaviour between room temperature and 600 °C. A post-processing tool was used in which the plasticity induced crack opening level was calculated, followed by a calculation of the effective Δ J range for each crack length. The adopted procedure yields good correlation between the different tests, under both isothermal and non-isothermal conditions.